Time Management in Academic Activities of Full Time Working Students - Hardiningrum, Iing Sri; Mukhlis, Imam (PT FORMOSA CENDEKIA GLOBAL, 2023)
Study This aim for now management management time on activities academic student worker full time. Study This use approach qualitative descriptive. Data collection techniques in research This use observation, interviews and documentation. Study This conducted at Kadiri Islamic University Kediri with amount sample of 45 respondents. Research result This show that Most student Not yet capable carry out management management time with good and partial Again Already capable carry out management management time with good.